Illegal activity in the UK halal (sheep) supply chain: Towards greater understanding. (May 2017) - McElwee, Gerard; Smith, Robert; Lever, John
Highlights: Two groups of suspects in farm theft. Urban-marauders and industry insiders or rogue-farmers. Food-fraud is a collective term encompassing the deliberate misrepresentation of food for economic gain. The illegal halal trade is also referred to as the 'Smokies' Trade. Smokies are sheep slaughtered illegally without stunning. Abstract: Food supply chain theory and practice assumes that the processes involved are legal and value adding . In this paper, using examples from the UK halal (sheep) meat supply chain, we outline a value extracting value chain through a mixed methods qualitative approach consisting of face-to-face-interviews and a documentary research strategy underpinned by Narrative Inquiry . Building on previous theoretical work on Illegal Rural Enterprise, we present a narrative of an individual rogue-farmer, and explore his involvement in the illegal halal ('smokies') trade over a fifteen-year period. The paper provides a compelling story that will enable investigators to better understand illegal enterprise from a supply chain perspective and more adequately address the concerns stated in the UK Fraud Act 2006. The paper will be useful to food standards agencies in that furthers our understanding of entrepreneurial practice and morality in the food industry. The results demonstrate that illegal rural enterprise is a multi-faceted concept that requires an understanding of business practices and processes alongside a multi-agency approach to enterprise orientated crime. Our approach suggests that supply chains can be 'flipped' in order to understand illegal processes in addition to conventional legal processes.